2001
DOI: 10.1007/s003300101102
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of lymphadenopathy in the neck

Abstract: Imaging is playing a major role in the assessment of cervical lymphadenopathy. In infectious disease, the assessment of abscess formation and the relation of the abscess to surrounding vital structures is crucial for its management. In head and neck malignancies, imaging can be helpful for staging. Imaging of the neck for the assessment of nodal metastases can be used to detect occult metastases or to assess operability of palpable metastases. The detection of small occult metastases has limitations, as microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 83 publications
3
81
1
Order By: Relevance
“…Between 40% and 60% of all occult metastases are found using either CT or MRI at the cost of a relatively high rate of false positives. 6 In contrast, USgFNAC has a higher sensitivity and specificity and is more cost-effective than CT and MRI. In experienced hands, the sensitivity for the N0 neck can reach 73% with a specificity of 100%, 7 although others reported sensitivities ranging from 42% to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Between 40% and 60% of all occult metastases are found using either CT or MRI at the cost of a relatively high rate of false positives. 6 In contrast, USgFNAC has a higher sensitivity and specificity and is more cost-effective than CT and MRI. In experienced hands, the sensitivity for the N0 neck can reach 73% with a specificity of 100%, 7 although others reported sensitivities ranging from 42% to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neck dissection with subsequent pathological examination remains the criterion standard for node staging. [37][38][39] Diagnostic performance of imaging studies are difficult to compare owing to a variety in study designs, study populations, imaging modalities and techniques. 29,36 In conclusion, the study has found differences between the N-stage performed by OMRs and MRs.…”
Section: Discussionmentioning
confidence: 99%
“…26 Finally, US has the unique advantage of real-time pathologic correlation via US-guided FNAC, which can be instantly analyzed and, if necessary, repeated and confirmed with multiple passes within the timeframe of a single study. 27 For reasons of cost and efficiency, US generally has been used more liberally in Europe than in the United States 28,29 and has been proposed as a follow-up strategy for the neck in some international forums. 30,31 Specifically in the postradiation setting, one older study established that the effects of preoperative irradiation could be identified by using morphologic changes visualized on US.…”
Section: Discussionmentioning
confidence: 99%